Microbial diversity and ecology in hotspots - Gunjal, Aparna B., 1981-; Shinde, Sonali (Elsevier, Academic Press, an Imprint of Elsevier, 2022)
Microbial Diversity in Hotspots provides an introduction to microbial diversity and microbes in different hotspots and threatened areas. The book gives insights on extremophiles, phyllosphere and rhizosphere, covers fungal diversity, conservation and microbial association, focuses on biodiversity acts and policies, and includes cases studies. Microbes explored are from the coldest to the hottest areas of the world. Although hotspots are zones with extremely high microbiology activities, the knowledge of microbial diversity from these areas is very limited, hence this is a welcome addition to existing resources.